Peasant Resilience: Decolonization and Re-conceptualization - Santiago Vera, Teresita; Rosset, Peter Michael [UNESP]; Moreno, Antonio Saldivar; Mendez, Victor Ernesto (Mary Ann Liebert, Inc, 2021)
The objective of this article is to re-read and take initial steps toward decolonizing the concept of resilience from a peasant perspective. Resilience has origins in the Western, Cartesian, and capitalist paradigms, and we examine the concept from a peasant world partially situated outside of capitalist social relations. In conventional usage, resilience signifies returning to the previous state after disturbance, yet for those not favored by power, wealth, and inclusion in larger society, that is hardly a satisfactory goal. To be useful in the case of peasant societies, we argue that the concept must be re-formulated based on an understanding of the peasant condition, informed by decolonial thought, and with methodologies for epistemic decolonization. We argue that what we call peasant resilience is significantly related to relative autonomy.
Keywords: peasant agriculture; peasantry; autonomy; resilience; Eurocentrism; Chayanovian balances